COMPARATIVE EFFECTIVENESS RESEARCH: A-MATTER-OF-BALANCE AND FIT AND STRONG. (11th November 2018) - Lee, S; Towne, S; Smith, M; Ory, M
Abstract: Many lifestyle enhancement programs for older adults have been developed and evaluated, yet, there is limited comparative effectiveness research to help inform older adults and other stakeholders when making decisions about program choices. Hence, this study aims to compare two existing evidence-based programs, A Matter-of-Balance (AMOB) and Fit & Strong! (FS), both of which have physical activity (PA) components and shown improvements in mobility. This study used the pre-post data from a community-service project (2013–2017) to conduct comparative-effectiveness analyses with 312 AMOB and 141 FS participants. The primary outcome variables were mobility, measured using Timed-Up-and-Go test, and self-reported PA (minutes per week). Multiple multi-level regression models were used to compare differences in pre-post improvements for mobility and PA between AMOB and FS participants, controlling for participant- and class-related factors. Overall, the average age of participants was 75 years (60–90 years), and the majority were female (79%). No significant difference were observed for PA levels across programs (p>0.05). However, compared to the FS participants, the AMOB participants showed significantly less improvement in mobility (p<0.05), after adjusting for age, attendance, and baseline mobility at both participant- and class-levels. Findings suggest that evidence-based programs with more physical activity programming have greater benefits for improving mobility. Results have implications to create strategies that purposively recruit and enroll older adults into programs that meet their specific demands. More comparative effectiveness research is needed to identify program-specific benefits regarding cost-effectiveness and other broader measures (e.g., fear of falling, falls, self-efficacy, quality of life).